2016
DOI: 10.1155/2016/3128280
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Ameliorates Transplant Arteriosclerosis in Vascular Allograft Transplantation by Regulating the NO/cGMP Pathways and Rho‐Associated Kinases Expression

Abstract: Objective. Transplant arteriosclerosis is considered one of the major factors affecting the survival time of grafts after organ transplantation. In this study, we proposed a hypothesis of whether lycopene can protect grafted vessels through regulating key proteins expression involved in arteriosclerosis. Methods. Allogeneic aortic transplantation was performed using Brow-Norway rats as donors and Lewis rats as recipients. After transplantation, the recipients were divided into two groups: the allograft group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Inflammation is related to atherosclerosis, arterial stiffness, and major cardiovascular events. The anti-inflammatory role of lycopene was demonstrated by several studies (Hung et al, 2008 ; Kim et al, 2010 ; Xu et al, 2012 ; He et al, 2016 ). Hung et al revealed that lycopene can inhibit TNF-alpha induced NF-kappa B activation, expression of intracellular adhesion molecule-1 (ICAM-1), and interaction between monocytes and endothelial cells, which might explain the cardiovascular benefits of lycopene (Hung et al, 2008 ).…”
Section: Cardiovascular Protective Mechanismsmentioning
confidence: 91%
See 2 more Smart Citations
“…Inflammation is related to atherosclerosis, arterial stiffness, and major cardiovascular events. The anti-inflammatory role of lycopene was demonstrated by several studies (Hung et al, 2008 ; Kim et al, 2010 ; Xu et al, 2012 ; He et al, 2016 ). Hung et al revealed that lycopene can inhibit TNF-alpha induced NF-kappa B activation, expression of intracellular adhesion molecule-1 (ICAM-1), and interaction between monocytes and endothelial cells, which might explain the cardiovascular benefits of lycopene (Hung et al, 2008 ).…”
Section: Cardiovascular Protective Mechanismsmentioning
confidence: 91%
“…Tomato products reduced oxidative stress related to postprandial lipemia and the associated inflammatory reaction in a study including normal weight participants (Burton-Freeman et al, 2012 ). He et al reported the benefits of lycopene in preventing transplant vasculopathy, demonstrating that intimal hyperplasia and smooth muscle cell proliferation were reduced by the administration of lycopene and the infiltration of inflammatory cells in allograft vessels was reduced in an animal model (He et al, 2016 ). Lycopene can ameliorate allograft atherosclerosis via downregulating Rho-associated kinases and regulating the expression of key factors through NO/cGMP pathways (He et al, 2016 ).…”
Section: Cardiovascular Protective Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remarkably lessened the expression of ROCK1, Ki-67, ICAM-1 and ROCK2, whereas it improved the expression of eNOS-implanted arteries and cGMP plasma concentration. In summary, lycopene is able to improve the vascular arteriosclerosis in the case of allograft transplantation by downregulating the expression of Rho-related kinases and by regulation of the NO/cGMP pathways expression, as well [61].…”
Section: Cardioprotectivementioning
confidence: 97%
“…Several studies reported that when tomatoes were fed to hens, lycopene was accumulated in egg yolk (Akdemir, Orhan, Sahin, Sahin, & Hayirli, ; Gregosits et al, ; Kang, Kim, Cho, Yim, & Kim, ; Karadas et al, ; Olson, Ward, & Koutsos, ). Lycopene has especially high singlet oxygen quenching activity among various common carotenoids (Aizawa et al, ), and the dietary intake of this carotenoid offers many health benefits such as decreased risk of some cancers and arteriosclerosis (He et al, ; Wang, Cui, Xiao, Fang, & Xu, ). Hence, the intake of lycopene‐rich egg could lead to health promotion for humans.…”
Section: Introductionmentioning
confidence: 99%